THE EFFECTIVENESS OF E-SERVICE QUALITY, PROMOTION MIX, AND BRAND AWARENESS ON REPEAT PURCHASE INTEREST IN THE DANA APPLICATION - Abu Risky, Farhan; Syah, Hidayat; Sani, Abdillah (DESANTA (Indonesian of Interdisciplinary Journal), 2024)
This study discusses e-wallet. With the current development and rapid and rapid technological advances, it has greatly influenced major changes in people's daily activities, towards the digital world in all aspects. One of them is in the financial technology industry. This financial technology is in the form of electronic banking products that enable digital payments in transactions. DANA is one of the leading electronic banking products in Indonesia. Based on the results of observations, problems were found related to E-service Quality, Promotion Mix, Brand Awareness and Repurchase Interest in the DANA application. The purpose of this study was to determine the partial and simultaneous effects of E-service Quality, Promotion Mix, Brand Awareness and Repurchase Interest on the DANA Application. This study is a descriptive study using quantitative methods. and uses a Likert scale to measure. The sampling method uses a non-probability sampling technique, namely the type of random sampling of the population used is infinity population, which means a population whose number is unknown. The population in this study were all Dana application users with 120 respondents. The analysis model with Partial Least Square mode with the type of Structural Equation Modeling (PLS-SEM) equation modeling, processed with the SmartPLS version 4.1.0.6 program. The results of the R-square Value of Repurchase Interest show 0.961 (96.1%) The results of this study indicate that E-service Quality, Promotion Mix, Brand Awareness have a significant positive effect on Repurchase Interest in the DANA Application